Fertility sparing treatment in an infertile patient with severe adenomyosis and a uterine fibroid: a case report - Yaramareddy, Swapna; Siyonu Kumari Sardena,; Nom Kumar Naik Bhukya,; Tulasi Ram Naik Menavath, (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Adenomyosis and uterine leiomyoma are benign lesions of the myometrium. Adenomyosis is a myometrial lesion characterised by the presence of ectopic endometrium with or without hyperplasia of the surrounding myometrium. Uterine fibroids, also called leiomyomas or myomas, are benign tumours that arise from the smooth muscle of the uterus. A 33-year-old nulliparous woman attended the clinic with primary infertility for 18 years. She was diagnosed with severe adenomyosis and uterine fibroids. She conceived successfully after undergoing in vitro fertilization (IVF) and a downregulated frozen embryo transfer (FET). Adenomyosis is a common cause of primary and secondary dysmenorrhea associated with infertility in young, nulliparous women. Fertility preservation is the primary goal in this population. Medical management is essential, and a properly downregulated and planned FET is the treatment of choice.